Wars of the Middle Ages - Vladimir Kuzmich Karnaukh (Управленческое консультирование, 2018)
The article discusses the role of war in the life of medieval society. Particular attention is paid to the human dimension of war. The author notes the characteristics of war in the Middle Ages. The article highlighted the distinctive features of the war in the West and in the East, examines the ethical issues of the war, the factors are considered, ensure the emergence of chivalry.